21st International Conference on Silicon Carbide and Related Materials (ICSCRM 2024) - Victor Veliadis; Arash Salemi (Trans Tech Publications Ltd, 2025)
Selected peer-reviewed extended articles based on abstracts presented at the 21st International Conference on Silicon Carbide and Related Materials (ICSCRM 2024)Aggregated Book